Концепт на откривање сентинелен лимфен јазол со радиоколoид обележан со 99mTc кај карцином на дојка, малиген меланом и колоректален карцином - воведување и стандардизација на методот - Стојаноски, Синиша (Медицински факултет, УКИМ, Скопје, 2017)
INTRODUCTION: The sentinel lymph node is the first node from the locoregional lymphatic basin in which the tumor cells occure with highest probability, as metastatic/micrometastatic deposits, after the lymphatic spread from the primary tumor location. Precise detection and detailed pathohistological evaluation of the sentinel lymph nodes provides valid information regarding the status of the regional node basin (metatstatic/micrometastatic involvement) and determines the extent of the surgical procedure (selective or radical lymphadenectomy) AIM: To introduce the sentinel lymph node detection method using 99mTcradiolabeled colloids in breast carcinoma, malignant melanoma and colorectal carcinoma patients. To validate and standardize the sentinel lymph node detection method using 99mTc-radiolabeled colloids in breast carcinoma, malignant melanoma and colorectal carcinoma patients. (to present the sensitivity, specificity, accuracy, negative predictive value and the detection rate of the method). To implement the sentinel lymph node detection method using 99mTc-radiolabeled colloids into the appropriate surgical guidelines and oncology protocols. MATERIAL AND METHODS: Prospective (longitudinal interventional randomized study) analysis was performed on 230 patients (110 breast carcinoma patients, 80 malignant melanoma patients and 40 colorectal carcinoma patients). Learning curve was performed in all three groups of patients. (with obligatory radical lymphadenectomy and without implementation of the preserving surgical techniques regardless of the status of the sentinel lymph nodes). All patients were classified as T1-2, N0, M0 according to the inclusion criteria. Preoperative detection of the sentinel lymph node and lymphatic drainage mapping was performed in all patients (4h prior to operation in breast carcinoma and malignant melanoma patients and 17-24h prior to operation in colorectal carcinoma patients). The method included application of 4 mCi nanosized sentiscint sulphur colloid labelled with 99mTc at 4 locations: periareolar (intradermal) / peritumoral (in patients with breast carcinoma and malignant melanoma) or submucose / intratumoral in colorectal carcinoma patiens using the endoscopic (colonoscopic) technique. The dynamic phase followedvthe application of the tracer, and was used for lymphatic drainage mapping. It was performed using the acquisition protocol of 30 minutes / 30 frames / 60 seconds per frame at 256x256x16 matrix. The static acquisitions (300seconds or 600seconds per position) were performed at AP, PA and lateral positions at predefined time points (30minutes, 1h and 2 h post injection in breast carcinoma and malignant melanoma patients, and at 17-24h post injection in colorectal carcinoma patients). The body contures were delineated using the separate flood cobalt source and the sentinel lymph node mapping was performed using the gamma probe. The probe was used also for radioguided surgery and sentinel lymph node operative extirpation. We used blue dye as additional tracer for sentinel lymph node visualisation in order to increase the sensitivity and specificity of the method. Ex tempore histopathological analysis was performed in breast carcinoma patients and detailed H&E and immunohistochemistry post operation in all 3 gropus of patients in order to determine the status of the sentinel lymph node, the extent of the surgical intervention and the postoperative oncology protocols. RESULTS: The sensitivity of the method in breast carcinoma patients was 92,86%, specificity was 100%, negative predicitive value was 98,9%, false negative rate was 1,05%, accuracy was 99% and the identification rate was 98,2%. The preserving surgical technique was performed in 94 of 110 patients (85,5%). The detection rate of the method in malignant melanoma patients was 100%, sensitivity was 96,6%, specificity was 100%, accuracy was 98,8%, negative predictive value was 98,1% and the false negative rate was 1,96%. The preserving surgical technique was performed in 51 of 80 patients (63,75%). The sensitivity of the method in colorectal carcinoma patients was 83,3%, accuracy was 92,1%, negative predictive value was 86,95%, detection rate was 95% and the false negative rate was 7,5%. Staging improvement rate was 22,5%. CONCLUSIONS: The sentinel lymph node detection method presented high detection rate, sensitivity, specificity, accuracy, negative predictive value and low false negative rate. Therefore it is a valid, precise and reliable diagnostic modality in early staged breast carcinoma, malignant melanoma and colorectal carcinoma patients promoting the minimally invasive surgery concept. The acquisition protocol for this method was standardized and recommended for routine use at our institution in the field of radioguided surgery.
Sentinel lymph node detection concept in patients with breast carcinoma, malignant melanoma and colorectal carcinoma using the 99mТc-radiolabeled colloids – implementation and standardization of the method
Докторска дисертација одбранета во 2017 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Даниела Поп Ѓорчева.
Keywords: sentinel lymph node, 99mTc-SentiScint, blue dye, breast carcinoma, malignant melanoma, colorectal carcinoma